Learned helplessness reveals a population at risk for depressive-like behaviour after myocardial infarction in mice - Bruns, Bastian; Schmitz, Thomas; Diemert, Nathalie; Schwale, Chrysovalandis; Werhahn, Stefanie; Weyrauther, Friederike; Gass, Peter; Vogt, Miriam A.; Katus, Hugo; Herzog, Wolfgang; Backs, Johannes; Schultz, Jobst-Hendrik (ESC heart failure, 2019)
Aims Myocardial infarction (MI) and heart failure (HF) are risk factors for the development of depression, additionally worsening the quality of life and patient outcome. How HF causes depression and how depression promotes HF remain mechanistically unclear, which is at least partly caused by the difficulty of in vivo modelling of psychosomatic co-morbidity. We aimed to study the potential sequence of events with respect to different depression aspects upon HF. Methods and results Male C57BL6 mice underwent MI, followed by behavioural and echocardiographic characterization. Motility, exploration, and anxiety-like behaviour were unaffected in mice after MI. We did not observe increased depressive-like behaviour in the sucrose preference, tail suspension, or Porsolt forced swim test. Mice did not display signs of learned helplessness (LH) when compared to sham. Accordingly, cluster analysis revealed only a slightly higher quota of LH in HF (38%) vs. sham mice (32%). But strikingly, three-group cluster analysis revealed an additional intermediate subpopulation at risk for LH after HF (29%). Interestingly, this population featured elevated cardiac expression of nr4a1. Conclusions The LH paradigm uncovered a subtle predisposition to depressive-like behaviour after MI, whereas testing for anhedonia and despair was insufficient to show a behavioural shift in mice. Therefore, we suggest an accumulating risk profile and a multiple-hits hypothesis regarding the pathogenesis of co-morbid depression after MI. Symptoms of LH may present a marker of subclinical depression after MI, the impact of which remains to be investigated. The proposed sequence of behavioural testing enables the mechanistic dissection of cardio-psychogenic signalling in the future.